Serendipity in rhetoric, writing, and literacy research - Goggin, Maureen Daly; Goggin, Peter N. (Utah State University Press, 2018)
"Scholars have known moments of surprise, catastrophe, or good fortune, though they seldom refer to these occurrences in reports or discuss them. Revealing the different kinds of work scholars, particularly those in rhetoric, need to do to recognize a serendipitous discovery or a missed opportunity"--Provided by publisher